Pengaruh E-WOM dan Trust terhadap Purchase Intention dalam Belanja Online - Annisa Annisa; Mirzam Arqy Ahmadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Noteworthy changes in customer behavior due to the advancement of data and communication innovation have driven to an increment in online shopping, particularly amid the Covid-19 widespread. This ponder points to analyze the impact of electronic word-of-mouth (e-WOM) and believe on buy deliberate within the setting of e-commerce in Indonesia. With information appearing a surge in exchanges on different marketplaces, this consider distinguishes that positive e-WOM can increment buy deliberate, whereas negative e-WOM tends to diminish it. In expansion, consumers' level of believe in online shopping stages emphatically impacts buy choices. The discoveries appear that both e-WOM and believe have a critical positive impact on buy deliberate. The comes about of this consider give experiences for companies to develop effective promoting techniques to extend buy deliberate and construct shopper believe within the computerized time.